About the Russian and the Russian style - Bagina, Elena (project baikal, 2023)
The external and internal image of Russia and the Russian influences the formation of national identity. The search for Russian identity in architecture in the nineteenth century gave rise to numerous artificial “Russian styles” created within the eclectic method. A special role was played by the Byzantine movement, since it was in Byzantium where the roots of Russian culture and Russian nationhood were looked for. A single Russian style does not exist, as well as a German style or an American style. An artificial search for the Russian in architecture is conditioned by ideology and current politics. We say: Russian Classicism, Russian Avant-garde, Russian Baroque, Russian Modernism, thereby underlining not only the location of objects but also those traits that are identified as Russian.